A Dual-Polarized Horn Antenna Covering Full Ka-Band Using Turnstile OMT - Xiao, Jun; Teni, Geer; Li, Hongmei; Ding, Tongyu; Ye, Qiubo (Frontiers in Physics, 2022)
This letter presents a dual-polarized corrugated horn antenna incorporated a turnstile orthomode transducer (OMT) covering full Ka-band (26.5-40 GHz). A three-stepped cylindrical tuning stub scattering element is designed in the turnstile junction to combine/split the two linearly polarized waves with high isolation. The proposed turnstile OMT shows a good simulated return loss better than 20 dB and a high isolation higher than 57 dB within the whole Ka-band. Then, a corrugated horn antenna with five-stage choke rings is designed. Finally, the proposed horn antenna incorporated the turnstile OMT is fabricated and measured. The measured impedance bandwidth for |S11/22|≤-15dB is 50.7% from 25 to 42 GHz. The measured peak gain is 11.9 dBi. The proposed antenna system is a promising candidate for the 5G millimeter-wave applications.